2019
DOI: 10.1038/s41598-018-37053-0
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Uric Acid is Highly Associated with a Reduced Left Ventricular Ejection Fraction Rather than Increased Plasma B-type Natriuretic Peptide in Patients with Cardiovascular Diseases

Abstract: High serum uric acid (UA) has been reported to be associated with left ventricular (LV) dysfunction; however, the relationship between UA and plasma B-type natriuretic peptide (BNP), a sensitive biomarker of heart failure, is still unclear. This study investigated their relationship to provide an accurate assessment of high UA. The study patients consisted of 3,077 subjects who underwent cardiac catheterization because of various cardiovascular disorders. Since the explanatory factors of multiple regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…43,44 Uric Acid A number of studies indicated a significant association between high UA levels and cardiac functions in patients with cardiovascular disease. [23][24][25] However, our study showed that UA levels did not correlate with morphology, LVEF, or GLS in disease-free obese adolescents, even though higher levels were observed in obese subjects. These results support the Framingham Heart Study findings demonstrated that UA does not correlate with the risk of cardiovascular disease, at least in men.…”
Section: Leptin and Cardiac Functioncontrasting
confidence: 63%
See 1 more Smart Citation
“…43,44 Uric Acid A number of studies indicated a significant association between high UA levels and cardiac functions in patients with cardiovascular disease. [23][24][25] However, our study showed that UA levels did not correlate with morphology, LVEF, or GLS in disease-free obese adolescents, even though higher levels were observed in obese subjects. These results support the Framingham Heart Study findings demonstrated that UA does not correlate with the risk of cardiovascular disease, at least in men.…”
Section: Leptin and Cardiac Functioncontrasting
confidence: 63%
“…Cicoira et al demonstrated that UA levels correlate with diastolic but not systolic dysfunction in ischemic cardiomyopathy patients, whereas other studies found a relationship between UA levels and LVEF in patients with ischemic heart disease and heart failure. [23][24][25][26] However, the relationship between UA and cardiac functions in healthy obese people has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The path analysis was performed using the IBM SPSS AMOS software program (version 25, Amos Development Corporation, Meadville, PA, USA). We have previously described how to write a path model [5][6][7][8][9][10][11][12][13][14] . In brief, the current models show the relationship between clinical factors and the LV cavity sizes or LVEF using some hierarchical regression models.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…
of a path diagram due to the solution of some disease status [5][6][7][8][9][10][11][12][13][14] . In this study, we tried to examine the effect of respective risk factors, such as aging, gender difference, body mass index (BMI), hypertension, diabetes, and dyslipidemia, on LV cavity sizes at the timing of systole and diastole in patients with IHD by using SEM.
…”
mentioning
confidence: 99%
“…Gender, BMI, HR, LVEF, and LVEDP are widely known to be major determinants of BNP [20][21][22] . Since we recently reported that BNP might be related to HOMA-IR and UA, these two factors were also included in the path diagram [23][24][25] . We excluded patients with arterial fibrillation (AF) (n = 1) and those receiving insulin therapy (n = 8) to reduce possible bias.…”
Section: Concept Of the Proposed Path Model A: Investigation Of The Imentioning
confidence: 99%